Is Vitamin A Supplementation Associated with Anemia in Children Under Five Years of Age in Peru: Secondary Analysis of the "Demographic Health Survey" 2015-2018? - Ribaudo Quimper, Isabella (2022)
Vitamin A deficiency (VAD) affects 12% of Peruvians under five years of age. Recent studies have shown an association with hematopoiesis and iron metabolism. In Peru, three-quarters of a million children have anemia. We aimed to identify an association between Vitamin A supplementation (VAS) and anemia in children under five years of age. A cross-sectional secondary analytical study from the Peruvian Demographic Survey and Family Health (DHS) was conducted. The primary outcome, anemia, was measured through hemoglobin concentration and adjusted by altitude. The DHS interviewer ensured the participant’s VAS in the last six months through a structural healthcare card. The association was statistically significant using crude regression but disappeared when adjusted per socioeconomic level and gender. VAS was not significantly associated with a lower prevalence of anemia. Further studies are required to help identify the association between VAS and anemia.